2020
DOI: 10.3390/jcm10010007
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Standardized Post-Cesarean Delivery Order Set with Multimodal Combination Analgesia Reduces Inpatient Opioid Usage

Abstract: Background: Opioid use has emerged as a leading cause of death in the US. Given that 1 in 300 opioid-naive patients exposed to opioids after cesarean birth will become persistent users, hospitals should strive to limit exposure to these medications. We set out to evaluate whether transitioning to a standardized order set based on multimodal combination analgesic therapy decreases the exposure to opioids after cesarean delivery. Methods: Our health system’s post-cesarean pain management electronic medical recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
9
0
2
Order By: Relevance
“…Improved patient satisfaction is a very important goal of ERAS protocols and our results showed better overall satisfaction in group E than in group C; this resulted in higher reported recommendation levels among family and friends. This has also been previously noted in prior reporting about ERAS after cesarean delivery, as described by Bollag et al2 9 and Sultan et al 30 .…”
Section: Discussionsupporting
confidence: 82%
“…Improved patient satisfaction is a very important goal of ERAS protocols and our results showed better overall satisfaction in group E than in group C; this resulted in higher reported recommendation levels among family and friends. This has also been previously noted in prior reporting about ERAS after cesarean delivery, as described by Bollag et al2 9 and Sultan et al 30 .…”
Section: Discussionsupporting
confidence: 82%
“…The 8 studies that evaluated multimodal stepwise interventions were all retrospective cohort studies 16–23 and included initiating scheduled ibuprofen and acetaminophen, with the administration of an opioid on an as‐needed basis for breakthrough pain. These interventions include multiple changes in a bundled fashion and specified stepwise approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies identified interventions to reduce postpartum opioid use during the inpatient period. The majority included implementation of multimodal stepwise protocols (n = 8) [16][17][18][19][20][21][22][23] or changes in dosages or timing of medication administration (n = 4). [24][25][26][27] Four additional studies included interventions that compared nonopioid medication with placebo, 28 use of lidocaine patches, 29 abdominal binder, 30 and battlefield acupuncture, in which needles are placed only on the surface of the ear (Table 1 ).…”
Section: Interventions To Reduce Postpartum Opioid Use During the Inp...mentioning
confidence: 99%
“…Obvladovanje poporodne bolečine je pomembno za kakovostno zdravstveno obravnavo, saj omogoča nemoteno povezovanje med otročnico in novorojenčkom in spodbuja dojenje (ACOG Committee Opinion, 2018;Wen, Yu, Kong, Liu, & Wei, 2020). Neustrezna analgezija po carskem rezu je lahko pomemben dejavnik tveganja za razvoj kronične bolečine, ki je povezana s poporodno depresijo in drugimi psihičnimi težavami (Eisenach et al, 2009;Holland et al, 2019;Bornstein et al, 2021). Večina analgetičnih režimov po carskem rezu vključuje opioidne analgetike.…”
Section: Uvodunclassified
“…Koncept multimodalne analgezije vključuje načrtno kombiniranje področnih tehnik lajšanja bolečine s sistemskimi analgetiki, različne farmakodinamične in farmakokinetične lastnosti z namenom doseganja sinergističnih analgetičnih učinkov (Holland et al, 2019;Smith, Young, Blosser, & Poole, 2019: Bornstein et al, 2021. Z multimodalnimi režimi analgezije lahko po carskem rezu pomembno zmanjšamo uporabo opioidnih analgetikov, ob tem pa še vedno zagotovimo ustrezno obvladovanje bolečine (Stopar-Pintarič et al, 2021;Višić, Stopar Pintarič, Albreht, Blajić, & Lučovnik, 2021).…”
Section: Uvodunclassified